(untitled) (Jurnal Pendidikan Fisika, 2021)
This study aims to improve the students’ physics learning outcomes using Macromedia flash learning media. This research is a classroom action research. The research subjects were students of class XI MIA 7 SMAN 2 Bantul, consisting of 30 people (20 Females and 10 Males). Data collection was carried out in three cycles, with three meetings each. The research stages include planning, implementing the action, observing, and reflecting. The results showed an increase in students’ learning outcomes after using Macromedia flash learning media. The percentage of students’ who achieved the minimum completeness criteria in cycle 1 was 83.3%. In Cycle 2, the percentage improved to 93.3%, and in cycle 3 became 96.7%. Therefore, it can be concluded that the use of Macromedia Flash can improve student learning outcomes.